Integrin and autocrine IGF2 pathways control fasting insulin secretion in β-cells - Arous, Caroline (J Biol Chem, 2021)
Elevated levels of fasting insulin release and insufficient glucose-stimulated insulin secretion (GSIS) are hallmarks of diabetes. Studies have established cross-talk between integrin signaling and insulin activity, but more details of how integrin-dependent signaling impacts the pathophysiology of diabetes are needed. Here, we dissected integrin-dependent signaling pathways involved in the regulation of insulin secretion in β-cells and studied their link to the still debated autocrine regulation of insulin secretion by insulin/insulin-like growth factor (IGF) 2–AKT signaling. We observed for the first time a cooperation between different AKT isoforms and focal adhesion kinase (FAK)–dependent adhesion signaling, which either controlled GSIS or prevented insulin secretion under fasting conditions. Indeed, β-cells form integrin-containing adhesions, which provide anchorage to the pancreatic extracellular matrix and are the origin of intracellular signaling via FAK and paxillin. Under low-glucose conditions, β-cells adopt a starved adhesion phenotype consisting of actin stress fibers and large peripheral focal adhesion. In contrast, glucose stimulation induces cell spreading, actin remodeling, and point-like adhesions that contain phospho-FAK and phosphopaxillin, located in small protrusions. Rat primary β-cells and mouse insulinomas showed an adhesion remodeling during GSIS resulting from autocrine insulin/IGF2 and AKT1 signaling. However, under starving conditions, the maintenance of stress fibers and the large adhesion phenotype required autocrine IGF2-IGF1 receptor signaling mediated by AKT2 and elevated FAK-kinase activity and ROCK-RhoA levels but low levels of paxillin phosphorylation. This starved adhesion phenotype prevented excessive insulin granule release to maintain low insulin secretion during fasting. Thus, deregulation of the IGF2 and adhesion-mediated signaling may explain dysfunctions observed in diabetes.